Impact analysis of DRG payment reform on hospitalization expenses and length of stay for lung cancer inpatients (2019–2023) - Chen, Mingbo; Pan, Dongfeng; Pan, Ting; Liu, Zhuo; Geng, Yuhui; Ma, Xiaojuan; Liang, Peifeng (Frontiers in Health Services, 2025)
ObjectiveGlobally adopted as a contemporary hospital management methodology, DRG payment systems aim to improve cost-efficiency, advance clinical service quality, and maintain treatment safety. Through empirical analysis of lung cancer inpatient data, this study quantifies the policy's effects on medical expenditure patterns and efficiency metrics, offering evidence-based insights for optimizing healthcare resource management.MethodsUsing ITS analysis, we developed a segmented regression model to evaluate the longitudinal effects of DRG-based payment reform on healthcare expenditure and LOS for lung cancer patients at a regional tertiary hospital in Northwest China.ResultsThe analytical cohort comprised 1,076 consecutively admitted lung cancer patients. ITS analysis revealed: (1) No significant immediate changes in total hospitalization costs (β2 = −1,365.532, P = 0.684), treatment expenses [(β2 = +147.512, P = 0.524)], or LOS [(β2 = −0.104 days, P = 0.944)], with stable longitudinal trends post-implementation; (2) Material expenses showed no reduction [(β2 = −1,433.072, P = 0.426)]; (3) Diagnosis expenses exhibited a significant immediate increase [(β2 = +1,953.740, P < 0.001)] and progressive monthly escalation [(β3 = +72.184, P = 0.035)], while drug costs showed a pronounced policy-induced surge [(β2 = +4,963.668, P < 0.001)] with accelerated growth [(β3 =+147.378 per month, P = 0.001)].ConclusionWhile DRG reform serves as an essential resource allocation mechanism, our findings reveal paradoxical outcomes. The implementation showed limited efficacy in reducing aggregate costs and LOS while provoking structural cost shifts marked by escalated diagnostic and pharmaceutical expenditures. These unintended economic consequences may distort clinical practices, potentially compromising both pharmacoeconomic efficiency and service quality.